The German contribution to the Spanish mining lexicon of the 18th century - Puche Lorenzo, Ángel Miguel (Romanica Olomucensia, 2016)
During the eighteenth century, science and technology experienced an important development that would be greatly expressed in the following century. However, not all areas of knowledge develop in the same way, or reflect the same changes. Mining was not oblivious to this fact and thus this is considered in our research. This time, it aims to contextualise and analyse the manuscripts by José de Ricarte and Juan Martin Hoppensack. Through them, the questions of how translations from German to Spanish worked and what consequences they could have had on the Spanish mining vocabulary are explored. In addition, how the teaching and research technicians or specialists fostered the incorporation of the new lexicon into Spanish will be highlighted.
Keywords: history of the Spanish language; history of the Spanish lexicon; history of science; mining.